PENGARUH KOMPENSASI, KOMITMEN ORGANISASIONAL, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi pada PT Teduh Makmur Semarang) - Dewi, Safrianisa; Rahardjo, Mudji (Diponegoro Journal of Management, 2015)
The purpose of  this  research  is  to  explain  how  the variable of  compensation,organizational commitment, and organizational culture influence to PT. Teduh Makmur Semarang employee performance. The data of this research were collected through a questionnaire distributed to 43 employees of PT. Teduh Makmur Semarang. This research used a saturated or census sampling method. The analysis method used is multiple linear regression.The result of this research shows that compensation, organizational commitment, and organizational culture influence positively and significantly to the employee performance. Variable used in this research give positive response,  meaning  that the compensation, organizational commitment, and organizational culture improving the performance  of  PT.  Teduh  Makmur  Semarang  employee.  Value  of  determination coefficient or R2 is 0,712, which means employee performance is affected by compensation, organizational commitment, and organizational culture amounted to 71,2%.Based  on  statistical  data  analysis,  found  that most  influential  variable is  thee variable of organizational commitment of 0,454, while the least influential variable is the variable of compensation of 0,393.